The impact of carbon trading policy on regional ecological risk: Synergy between market-based environmental policy and government intervention - Li, Linna; Jin, Xiaolin; Li, Yiming; Chen, Han; Wang, Yu (Frontiers in Environmental Science, 2022)
Eliminating or reducing ecological risks can help to observably guarantee the national security. In this article constructs a regional ecological risk evaluation framework is constructed on the basis of the PSR model from three dimensions: social, environmental and natural dimension, and the quantitative research method is taken to investigate the ecological risks in 30 Chinese provinces from 2006 to 2017. Taking the establishment of a carbon emission trading market as a quasi-natural experiment, the author further explores the impact of market-based environmental policies on regional ecological risks and their heterogeneity, channels of action, and the synergistic effects of government intervention. It is found that: (i) The implementation of market-based environmental policies can improve regional responsiveness to ecological risks and significantly reduce the level of regional ecological risks, meanwhile the research results pass the identification assumptions and robustness tests. (ii) The effects of market-based environmental policies are affected by the operational characteristics of market prices, liquidity and relative transaction scale. (iii)There are two essential approaches for market-based environmental policies to reduce regional ecological risks, named industrial structure upgrading and technology development. (iv) Moderate government intervention can produce synergistic effects in the process of regional ecological risk reduction by market-based environmental policies, and it is able to maintain intervention produces policy synergistic effects within a temperate condition. In a word, these findings can provide both an important basis for adjusting the implementation scope and operational structure of market-based environmental policies. On the other hand, it can also offer a significant policy insight for regional ecological risk evaluation and management.